The Analysis of Relationship between Economic Growh and Electricity Consumption in Africa by Ardl Method - BILDIRICI, Melike E (Energy Economics Letters, 2013)
This paper investigates the relationship between electricity consumption and economic growth by using Autoregressive Distributed Lag (ARDL) bounds testing approach and vector error-correction models (VECM) in Cameroon, Cote D’Ivoire, Congo, Ethiopia, Gabon, Ghana, Guatemala, Kenya, Senegal, Togo and Zambia for period 1970-2010. The ARDL results show that there is cointegration relation between electricity consumption and economic growth in ten of the eleven countries. The results reveal that income elasticities of electricity consumption, electricity consumption is luxury good for Gabon and Guetemela, necessity good or Engel’s good for Senegal and inferior good for Zambia. The causality analysis reports that growth hypothesis exists in Cameron, Congo Rep., Ethiopia, Kenya and Mozambique and the conservation hypothesis in Senegal and Zambia. For Gabon, Ghana and Guatemala, there exists the bidirectional causality between economic growtth and electricity consumption.